2016
DOI: 10.1111/pcmr.12483
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ induces SOX2 expression in a time‐dependent manner in human melanoma cells

Abstract: The sry-related high-mobility box (SOX)-2 protein has recently been proven to play a significant role in progression, metastasis, and clinical prognosis spanning several cancer types. Research on the role of SOX2 in melanoma is limited and currently little is known about the mechanistic function of this gene in this context. Here, we observed high expression of SOX2 in both human melanoma cell lines and primary melanomas in contrast to melanocytic nevi. This overexpression in melanoma can, in part, be explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Instead, SOX2 knockdown cells displayed reduced invasiveness, whereas SOX2 overexpression increased the invasion capacity of human melanoma cells 23 . In agreement with this, SOX2 was recently shown to mediate TGF-induced invasion in human melanoma cells 24 . Thus, at least in isolated melanoma cells, SOX2 has been implicated in either growth control or invasiveness, but its function in vivo remains to be elucidated.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Instead, SOX2 knockdown cells displayed reduced invasiveness, whereas SOX2 overexpression increased the invasion capacity of human melanoma cells 23 . In agreement with this, SOX2 was recently shown to mediate TGF-induced invasion in human melanoma cells 24 . Thus, at least in isolated melanoma cells, SOX2 has been implicated in either growth control or invasiveness, but its function in vivo remains to be elucidated.…”
Section: Introductionsupporting
confidence: 61%
“…Of note, studies performed solely in vitro or in combination with xenotransplantation assays provided controversial results, either implicating SOX2 in melanoma cell proliferation or invasion, or also failing to reveal a crucial role in melanoma as in our experiments performed with CRISPR-Cas-mediated knock out cells [20][21][22][23][24] . While the discrepancies between our work and previously published data could potentially be explained by different experimental settings 37 , they could also reflect the heterogeneity of melanoma and, thus, leave open whether SOX2 might fulfill a role in some cases of human melanoma.…”
Section: Sox2 Is Dispensable For Primary Tumor and Metastasis Formationmentioning
confidence: 99%
“…SOX genes have been demonstrated to be associated with the differentiation and proliferation of cells (30), and have oncogene functions (31,32). It is reported that SOX10 and SOX1 are tumor-associated antigens of melanoma and small cell lung cancer cells, respectively (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dedifferentiation of melanoma cells is assumed to enhance their malignant potential (Landsberg et al., 2012). Expression of single stem cell factors such as OCT4 or SOX2 increases melanoma stem cell properties, leading to a more aggressive tumor phenotype (Kumar et al., 2012, Santini et al., 2014, Weina et al., 2016). In contrast, the simultaneous expression of three pluripotency markers leading to a semi-stable pluripotent state reduces the tumor-initiating potential.…”
Section: Discussionmentioning
confidence: 99%